Records of the Women's Bureau of the Department of Labor, 1918-1965 - Sealander, Judith; Grinder, Dale; Hydrick, Blair (Research collections in women's studies., 1918)
Monthly reports, annual summaries, speeches, articles, research files, survey data files, correspondence files with private associations, labor unions, international organizations, and federal and state agencies and preparatory materials of Bureau-sponsored conferences.